Hubungan Peranan Dosen Di Kelas, Iklim Kelas, Dan Motivasi Belajar Terhadap Prestasi Belajar Mahasiswa Prodi PAUD IKIP PGRI JEMBER - Muarif, Syamsul; Sumiharsono, Rudy; Widiatsih, Asri (Universitas Nusantara PGRI Kediri, 2018)
Improving the quality of education in Higher Education has been pursued by various programs run by institutions. Some of the variables that affect learning achievement, among others, are the role of lecturers in the classroom, classroom climate, and student learning motivation. In this context, the purpose of this research is to know the direct relationship between: 1) the role of lecturer in class with learning motivation, 2) role of lecturer in class with class climate, 3) class climate with learning motivation, 4) learning motivation with achievement learning, 5) role of lecturer with learning achievement through learning motivation, 6) class climate with learning achievement through learning motivation. The design of this study used a quantitative survey method, a correlational type. Determination of research area using purposive sampling method area. As a research population is a student of PAUD IKIP PGRI Jember semester even academic year 2015/2016. The number of university students in 2014 is 472 students and taken 205 people as sample. Sampling using random sampling technique of lottery technique. To collect the data used questionnaire and analyzed using SEM (Structural Equation Modeling) analysis technique with AMOS 4.10 program. The conclusion of the research results are as follows: 1) the developed model is good (fit) based on index RMSEA 0.075 which means less than standard 0.08. This means that the model developed can be explained by the variables used in this study, 2) there is a direct relationship between: a) the role of lecturers in the classroom with learning motivation, b) the role of lecturers in the classroom with classroom climate, c) class climate with motivation to learn, d) learning motivation with learning achievement, e) indirect relationship between role of lecturer with learning achievement through learning motivation, f) indirect relationship between classroom climate with learning achievement through learning motivation.